KEBERLANJUTAN USAHATANI KAKAO DI DESA PUNCAK MONAPA KECAMATAN LASUSUA KABUPATEN KOLAKA UTARA - Juraeni Juraeni; Sukmawati Abdullah; Suriana Suriana (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The sustainability of cocoa farming in Puncak Monapa Village is of paramount importance for maintaining productivity, enhancing farmers' well-being, and sustaining the competitiveness of cocoa as a strategic commodity. The objective of this study is to ascertain the sustainability of cocoa farming in Puncak Monapa Village, Lasusua District, North Kolaka Regency. The research population consists of all cocoa farmers in Puncak Monapa Village, with a total sample size of 30 individuals. The research sample was obtained through the census method, yielding a total of 30 respondents. The present study employs a quantitative approach. The data collection techniques employed in this study include observation, interviews, and surveys administered via questionnaires. The variables in this study are the sustainability of farming, which includes economic, social, and environmental sustainability. The collected data is then processed using quantitative descriptive analysis techniques. The present analysis was executed by employing the class interval formula. The results indicated that the sustainability of cocoa farming in Puncak Monapa Village was satisfactory from the social, economic, and environmental perspectives. Farmers were able to build solid social networks, maintain economic stability through cost efficiency and product added value, and implement environmentally friendly practices such as the use of organic fertilizers and water conservation.